Economic Calculation Forecasting of Tourism: Example from Kazakhstan - Ayagoz Yerzhanovna Zhansagimova; Zhamilya Kaspievna Mizambekova; Aliya Sagundukovna Aktymbayeva; Jannat Muhamedzhanovna Bulakbay (Global Journal of Earth Science and Engineering, 2015)
Abstract: This article evaluates touristic – recreational potential of Kazakhstan and model of organizational forecast of tourist cluster. Interactions within the cluster lead to the development of new ways to compete and generate an entirely new opportunities to overcome isolation on domestic issues, inertia, inflexibility, and collusion between competitors that reduce or completely block the beneficial effects of competition and the emergence of new firms. Thus, the presence of the cluster allows domestic industry to maintain its advantage, and not give it to those countries that are more inclined to upgrade.